2020
DOI: 10.1021/acs.jpcc.0c08817
|View full text |Cite
|
Sign up to set email alerts
|

Graphene Oxide Membranes for Water Isotope Filtration: Insight at the Nano- and Microscale

Abstract: Recent experimental studies have revealed the selective permeation properties of lamellar graphene oxide (GO) membranes as applied to filtration of water isotopes. In this work, we explore the molecular structures and diffusive dynamics of water isotopes in GO membrane nanochannels by employing ReaxFF reactive molecular dynamics simulations. The significance of isotope effects and their role in the interactions between light/heavy water and the functional groups of GO membranes are identified, and it is found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 61 publications
0
14
0
Order By: Relevance
“…It should be noted that proton exchange between isotopic water molecules occurs, [14,41]. In the separation process, both HOD and D 2 O will be enriched as increasing the D/H in water will increase the likelihood for D 2 O to form, although, at low concentrations, HOD will be more common [42].…”
Section: Separation Performance Of Membranesmentioning
confidence: 99%
See 4 more Smart Citations
“…It should be noted that proton exchange between isotopic water molecules occurs, [14,41]. In the separation process, both HOD and D 2 O will be enriched as increasing the D/H in water will increase the likelihood for D 2 O to form, although, at low concentrations, HOD will be more common [42].…”
Section: Separation Performance Of Membranesmentioning
confidence: 99%
“…Membrane-based separation has been investigated as an alternative (e.g., to try to reduce costs and to try to simplify the process), particularly pervaporation and membrane distillation that have shown enhanced isotope separation with lower energy consumption due to the combined vapor pressure effect, diffusion effect and selective adsorption [13]. Chmieleswski et al reported that for water vaporizing inside the pores of the membrane [14], the vapor pressure effect is largely responsible for D separation from H and the diffusion effect is mostly responsible for 18 O separation from 16 O [15]. Due to the reported relatively large 18 O separation from 16 O achieved with membrane distillation, researchers have directed their attention into improving the efficiency of this process [16,17] and producing hydrophobic, polymer based-membranes to enhance isotopic water separation [18].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations